Future Interplanetary Space Weather Assets - Noé Lugaz (Space Weather)
Abstract Late 2019 and early 2020 have witnessed numerous developments regarding future interplanetary space weather missions in Europe and in the United States. In parallel, space weather‐related legislation is being considered in the United States. A summary of these developments is presented, and two related topical issues of Space Weather are introduced.